2004
DOI: 10.1158/1078-0432.ccr-0553-3
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatocyte Growth Factor Regulatory Factors in Human Breast Cancer

Abstract: Purpose: Hepatocyte growth factor (HGF) stimulates tumor cell-cell interactions, matrix adhesion, migration, invasion, and angiogenesis. This factor is produced as an inactive precursor called pro-HGF, which requires proteolytic conversion, by HGF activator (HGFA) and matriptase, to evoke a biological response. Two new HGFA inhibitors, HAI-1 and HAI-2, inhibit the generation of biologically active HGF, through their interaction with HGFA. This study determined the expression of this HGF regulatory system in br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
150
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(163 citation statements)
references
References 40 publications
(31 reference statements)
6
150
1
2
Order By: Relevance
“…The involvement of hepatocyte growth factor (HGF)-Met signaling in breast cancer biology has been well characterized (Parr et al, 2004). Increased cell proliferation, survival, motility, and extracellular matrix degradation resulting from the pathway activation contributes to tumor growth, invasiveness, and metastasis (Parr et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of hepatocyte growth factor (HGF)-Met signaling in breast cancer biology has been well characterized (Parr et al, 2004). Increased cell proliferation, survival, motility, and extracellular matrix degradation resulting from the pathway activation contributes to tumor growth, invasiveness, and metastasis (Parr et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Increased cell proliferation, survival, motility, and extracellular matrix degradation resulting from the pathway activation contributes to tumor growth, invasiveness, and metastasis (Parr et al, 2004). In fact, high levels of HGF and Met expression associated with invasive human breast cancer have been considered as possible indicators of earlier recurrence and shortened survival in these patients (Lindemann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental studies using medulloblastoma cells transfected with SPINT2 showed decreased proliferation, migration and anchorage-independent growth in vitro and increased survival times in mouse xenografts (Kongkham et al, 2008). Although SPINT2 downregulation has already been implicated in other human cancers (Dong et al, 2010;Morris et al, 2005;Parr et al, 2004) this was the first report to establish its role in medulloblastoma pathogenesis. Binning et al showed that HGF and Shh cooperate to transform cerebellar neural progenitors in transgenic mice, leading to medulloblastoma initiation and growth (Binning et al, 2008).…”
Section: Hgf/c-met Pathway In Medulloblastoma Formationmentioning
confidence: 88%
“…Activated HGF/SF binds to its receptor tyrosine kinase MET to induce dimerization and initiate phosphorylation cascades leading to comprehensive cellular changes that, in the deregulated context of cancer, drive malignant transformation and progression (73). HAI2 has been found to be a natural tumor suppressor in renal cell carcinoma (74), breast cancer (75,76), and prostate cancer (77,78), the loss of which leads to tumor growth and progression attributable at least in part to increased MET signaling. We have found mesotrypsin to be up-regulated with progression in prostate cancers and to contribute to invasion and metastasis (10), and it is highly plausible that these activities of mesotrypsin may be mediated at least in part through cleavage and inactivation of HAI2, with resulting increases in HGF/SF activation and MET signaling.…”
Section: Discussionmentioning
confidence: 99%